2014
DOI: 10.1063/1.4881474
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of edge localized mode burst times with divertor flux loop signal phase in JET

Abstract: A phase relationship is identified between sequential edge localized modes (ELMs) occurrence times in a set of H-mode tokamak plasmas to the voltage measured in full flux azimuthal loops in the divertor region. We focus on plasmas in the Joint European Torus where a steady H-mode is sustained over several seconds, during which ELMs are observed in the Be II emission at the divertor. The ELMs analysed arise from intrinsic ELMing, in that there is no deliberate intent to control the ELMing process by external me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(31 citation statements)
references
References 18 publications
4
27
0
Order By: Relevance
“…There is a lower cutoff in the ELM waiting time at Dt $ 10ms, and there are time intervals where ELMs occur less often (Ref. 16, and in other plasmas 12 ). Large ensemble statistical studies across many JET plasmas have also revealed 16,17 that the ELM waiting time probability distribution shows time structure, that is, some ELM waiting times are more likely than others.…”
Section: Elm and Full Flux Loop Time Signaturesmentioning
confidence: 99%
See 4 more Smart Citations
“…There is a lower cutoff in the ELM waiting time at Dt $ 10ms, and there are time intervals where ELMs occur less often (Ref. 16, and in other plasmas 12 ). Large ensemble statistical studies across many JET plasmas have also revealed 16,17 that the ELM waiting time probability distribution shows time structure, that is, some ELM waiting times are more likely than others.…”
Section: Elm and Full Flux Loop Time Signaturesmentioning
confidence: 99%
“…We determine the ELM occurrence times t k by identifying the peak of the Be II signal within each ELM using the method described in Ref. 16.…”
Section: Elm and Full Flux Loop Time Signaturesmentioning
confidence: 99%
See 3 more Smart Citations